The hospital almoner - Maule, Lilian A. (London : Kegan Paul, Trench, Trubner & Co.)
1904-09 1904 1900s 2 pages : illustrations OUR HOSPITALS AND CHARITIES VOL. I. — No. 8 SEPTEMBER, 1904 PRICE THREEPENCE THE HOSPITAL ALMONER THE creation of the post of "Hospital Almoner" is a welcome attempt to grapple with one of the most difficult of modern social problems, the organization of the hospital out-patient department. An "Almoner," the dictionary tells us, is "one who distributes alms on behalf of another," but the word as applied to the office in question has a definite and particular meaning of its own. It is, for instance, something quite distinct from the "inquiry officer" employed at some institutions to check the cases applying for medical relief, and for reasons to be presently explained represents a far wider and more intelligently conceived system. The hospitals at present employing almoners, who in each case are women of education and refinement, thoroughly trained for the work, are the Royal Free, St. George's, Westminster, and more recently the Metropolitan and the North Eastern Hospital for Children. To the Royal Free Hospital belongs the credit of instituting the new regime, and it is not too much to say that wherever it has been tried success has amply justified the experiment. The almoner's duty is systematically to interview the applicants for out-patient relief, "with a view to eliminate from among them those whose circumstances do not seem to entitle them to treatment, or who might be better provided for by a provident dispensary or by the Poor Law authorities." It will be readily understood by those who have studied the question of hospital abuse that the door is thus opened to a system which, properly conducted by competent persons, should secure to the community the utmost advantage from our splendid voluntary charities, whilst preventing their exploitation by those whose circumstances require treatment of another kind. The almoners work in connection with the Charity Organization Society, and this, which to some people who regard the C.O.S. methods as "hard and unsympathetic," will possibly create an objection, is really the pivot upon which the scheme turns. Consider the economy in endeavour which is gained by making use of an existing society, already, in every district, in touch with local machinery for becoming acquainted with the people and their needs. The almoner acts as a connecting link in a vast organization, through the operation of which the circumstances of every patient applying at any given hospital can be ascertained with the least loss of time. [photograph] MISS MUDD, ALMONER AT ST. GEORGE'S HOSPITAL. 378/IMSW/A/1/1/39